THE EFFECT OF Musa acuminata AND Ocimum basilicum MIXED EXTRACTS TO THE SURFACE HARDNESS OF BIOACTIVE COMPOSITE RESIN - Dewi Puspitasari; Maharani Laillyza Apriasari; Dewi Rahayu; Priyawan Rachmadi (Dentino : Jurnal Kedokteran Gigi, 2020)
ABSTRACTBackgrounds: The use of mouthwash daily may influence the mechanical properties of bioactive composite resin as a dental restoration, one of the mechanical properties is surface hardness. Herbal mouthwash can be used to minimize the side effect of mouthwash that contain alcohol. Mauli banana stem and basil leaf extracts can be produced into herbal mouthwash. Methods: Thirty specimens (10mm diameter x 2mm thick; n=5/group) bioactive composite resins were immersed in a mixed solution of Mauli banana and basil leaf extracts with concentration of 25%, 50%, 75 %%, 100%, the control group of chlorhexidine gluconate 0.2% and aquadest for 7 days in 37oC. Measurement of the surface hardness was using the Vickers Microhardness Tester with 100 gf load for 15 seconds. Results: One Way ANOVA and Post Hoc Bonferroni exhibited the significant differences (p <0.05) in hardness values between the specimens that immersed in the mixed solution Mauli banana and Basil leaf extracts, which in the concentration of 100% (4,49 ± 4,61 VHN) compared with 25% (38,20 ± 2,58 VHN), 50% (41,40 ± 3,84 VHN) and 75% concentration (40,40 ± 3,55 VHN). There was no siginificant difference (p >0.05) between specimens immersed in CHX, aquadest and the mixed solution of mauli banana and basil leaf extracts in all concentration. Conclusion: There is no change in bioactive composite resin surface hardness after immersed in the mixed solution of Mauli Banana stem (Musa acuminata) and Basil leaf (Ocimum basilicum) extracts.Keywords: Basil leaf extract, Bioactive resin, Mauli Banana stem extract, Surface hardness